The HLA-A*31:01 allele: influence on carbamazepine treatment - Yip VLM; Pirmohamed M (Dove Medical Press, 2017)
Vincent Lai Ming Yip,1,2 Munir Pirmohamed1,2 1MRC Centre for Drug Safety Science, Institute of Translational Medicine, Department of Molecular and Clinical Pharmacology, University of Liverpool, 2Department of Clinical Pharmacology,The Royal Liverpool and Broadgreen University Hospital NHS Trust, Liverpool, UK Abstract: Carbamazepine (CBZ) is an effective anticonvulsant that can sometimes cause hypersensitivity reactions that vary in frequency and severity. Strong associations have been reported between specific human leukocyte antigen (HLA) alleles and susceptibility to CBZ hypersensitivity reactions. Screening for HLA-B*15:02 is mandated in patients from South East Asia because of a strong association with Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). HLA-A*31:01 predisposes to multiple phenotypes of CBZ hypersensitivity including maculopapular exanthema, hypersensitivity syndrome, and SJS/TEN in a range of populations including Europeans, Japanese, South Koreans and Han Chinese, although the effect size varies between the different phenotypes and populations. Between 47 Caucasians and 67 Japanese patients would need to be tested for HLA-A*31:01 in order to avoid a single case of CBZ hypersensitivity. A cost-effectiveness study has demonstrated that HLA-A*31:01 screening would be cost-effective. Patient preference assessment has also revealed that patients prefer pharmacogenetic screening and prescription of alternative anticonvulsants compared to current standard of practice without pharmacogenetic testing. For patients who test positive for HLA-A*31:01, alternative treatments are available. When alternatives have failed or are unavailable, HLA-A*31:01 testing can alert clinicians to 1) patients who are at increased risk of CBZ hypersensitivity who can then be targeted for more intensive monitoring and 2) increase diagnostic certainty in cases where hypersensitivity has already occurred, so patients can be advised to avoid structurally related drugs in the future. On the basis of the current evidence, we would favor screening all patients for HLA-A*31:01 and HLA-B*15:02 prior to starting CBZ therapy. Keywords: carbamazepine, oxcarbazepine, hypersensitivity, adverse drug reaction, pharmacogenetics, HLA